Deviation of exchange rate and trade balance: evidence from the member countries of Gulf Cooperation council (GCC) Lencongan kadar pertukaran dan imbangan dagangan: bukti dari Negara Majlis Kerjasama Negara-Negara Gulf - Ummi Osman,; Tamat Sarmidi, (Institut Kajian Rantau Asia Barat, 2012)
Deviation or misalignment of the exchange rate has a different unwanted implication towards the economic growth. The right choice of exchange rate regime will bring an economy back to the equilibrium and many economists claim that it is one of the factors for the positive economic development. In contrast, a long term misalignment or deviation of the real exchange rate from the nominal rate can lead to severe macroeconomic imbalances, lead to speculation attack and against the orthodoxy of macroeconomic parities. However the empirical findings of previous studies with regards to the relationship of exchange rate and trade balance are not conclusive and are inconsistent for different countries. Although theoretically, the strengthening of a currency is expected to contribute towards the improvement of trade balance, there are other factors influencing the environment that might produce different outcome. The main objective of this paper is to analyse the long run relationship between deviation of exchange rate and trade balance in the Gulf Cooperation Council (GCC) member countries. The GCC is one of the important world markets. The economy of the GCC has developed tremendously in which the average gross domestic production (GDP) for the period of 1980 – 2008 is more than 300 percentages and Malaysia has a special interest in the region. Using the Purchasing Power Parity (PPP) model, we empirically identify that the currency of Saudi Arabia, Kuwait and Qatar at most of the time are overvalued while Bahrain and Oman are on the opposite. The study also shows that all GCC member countries are enjoying positive trade balance. Utilising two-step Engel-Granger cointegration technique we find a significant long run relationship between the exchange rate deviation and trade balance for most of the member countries in the long run but not in the short-run.